IMPACT OF MICROALGAL BIODIESEL CHARACTERISTICS ON EXHAUST PARTICLE EMISSIONS AND OXIDATIVE POTENTIAL IN DIESEL ENGINES (International Journal of Food and Nutritional Sciences, 2022)
Microalgae are considered to be one of the most viable biodiesel feedstocks for the future due to their potential for providing economical, sustainable and cleaner alternatives to petroleum diesel. This study investigated the particle emissions from a commercially cultured microalgae and higher plant biodiesels at different blending ratios. With a high amount of long carbon chain lengths fatty acid methyl esters (C20 to C22), the microalgal biodiesel used had a vastly different average carbon chain length and level of unsaturation to conventional biodiesel, which significantly influenced particle emissions, leading to similar total particulate matter (TPM) emissions as petroleum diesel, especially at higher blending ratios. In contrast, blends of up to 10% showed slight reductions in PM emissions. However, based on measurements of reactive oxygen species (ROS), the oxidative potential of particles emitted from the microalgal biodiesel combustion were lower than that of regular diesel. Biodiesel oxygen content was less effective in suppressing TPM emissions for biodiesels containing a high amount of polyunsaturated C20-C22 fatty acid methyl esters and generated significantly increased nucleation mode particle emissions. The observed increase in nucleation mode particle emission is postulated to be caused by very low volatility, high boiling point and high density, viscosity and surface tension of the microalgal biodiesel tested here. Therefore, in order to preserve PM emission benefits attributed to the use of biodiesel, this study recommends that the target composition of future microalgal biodiesel should not include FAMEs with high amounts of polyunsaturated long-chain fatty acids (≥ C20).